Aging‐related tau astrogliopathy (ARTAG): not only tau phosphorylation in astrocytes. (25th February 2018) - Ferrer, Isidro; García, Meritxell Aguiló; González, Irene López; Lucena, Daniela Diaz; Villalonga, Aina Roig; Tech, Margarita Carmona; Llorens, Franc; Garcia‐Esparcia, Paula; Martinez‐Maldonado, Alejandra; Mendez, Margalida Frau; Escribano, Benjamín Torrejón; Serra, Joan Josep Bech; et al.
Abstract: Aging‐related tau astrogliopathy (ARTAG) is defined by the presence of two types of tau‐bearing astrocytes: thorn‐shaped astrocytes (TSAs) and granular/fuzzy astrocytes in the brain of old‐aged individuals. The present study is focused on TSAs in rare forms of ARTAG with no neuronal tau pathology or restricted to entorhinal and transentorhinal cortices, to avoid bias from associated tauopathies. TSAs show 4Rtau phosphorylation at several specific sites and abnormal tau conformation, but they lack ubiquitin and they are not immunostained with tau‐C3 antibodies which recognize truncated tau at Asp421. Astrocytes in ARTAG have atrophic processes, reduced glial fibrillary acidic protein (GFAP) and increased superoxide dismutase 2 (SOD2) immunoreactivity. Gel electrophoresis and western blotting of sarkosyl‐insoluble fractions reveal a pattern of phospho‐tau in ARTAG characterized by two bands of 68 and 64 kDa, and several middle bands between 35 and 50 kDa which differ from what is seen in AD. Phosphoproteomics of dissected vulnerable regions identifies an increase of phosphorylation marks in a large number of proteins in ARTAG compared with controls. GFAP, aquaporin 4, several serine‐threonine kinases, microtubule associated proteins and other neuronal proteins are among the differentially phosphorylated proteins in ARTAG thus suggesting a hyper‐phosphorylation background that affects several molecules, including many kinases and proteins from several cell compartments and various cell types. Finally, present results show for the first time that tau seeding is produced in neurons of the hippocampal complex, astrocytes, oligodendroglia and along fibers of the corpus callosum, fimbria and fornix following inoculation into the hippocampus of wild type mice of sarkosyl‐insoluble fractions enriched in hyper‐phosphorylated tau from selected ARTAG cases. These findings show astrocytes as crucial players of tau seeding in tauopathies.